Two-hop AF MIMO relay systems with direct link-transceiver design based on new protocol - Zhang, J.; Liu, W.; He, Z.; Rong, Yue (2017)
In this paper, we study the transceiver design for two-hop amplify-and-forward (AF) multiple-input multiple-output (MIMO) relay systems using a new strategy, in which the source sends data at both time intervals. We propose a new alternating approach to design the transceiver and relay matrices based on the minimum mean-squared error (MMSE) criterion. We show through numerical simulations that the proposed system has a lower bit-error-rate compared with existing MIMO AF relay systems.